Ephrin type-A receptor 2-antisense RNA1/2 promote proliferation and migration of MDA-MB-231 cells through EPHA2-dependent Ras signaling pathway mediated by MAPK8/JNK1, MAPK9/JNK2-NFATC2/NFAT1 and JUND - Odaka, Tokifumi; Sakamoto, Ryou; Kumagai, Kazuhiro; Okuma, Kazu; Nishizawa, Mikio; Kimura, Tominori (Frontiers in molecular biosciences, 2024)
Ephrin type-A receptor 2 (EPHA2) is a receptor tyrosine kinase that is overexpressed in a variety of cancers, including breast cancer. EPHA2 expression may be causally related to tumorigenesis; therefore, it is important to understand how EPHA2 expression is regulated. We previously reported that EPHA2 antisense RNA (EPHA2-AS), a natural antisense transcript, is an important modulator of EPHA2 mRNA levels and hence production of EPHA2 protein. EPHA2-AS encodes two splice variants, EPHA2-AS1 and EPHA2-AS2. The two variants are constitutively expressed in a concordant manner with EPHA2 mRNA in human breast adenocarcinoma cell lines and in patient samples, with the highest levels detected in the basal-like/triple-negative molecular subtype of breast cancer cells. In this study, we investigated the mechanism of EPHA2-AS1/2 in triple-negative breast cancer using MDA-MB-231 cells. We performed RNA-seq transcriptome analyses of MDA-MB-231 cells treated with AHCC ® , which suppressed expression of EPHA2-AS1/2 and EPHA2 mRNA, and EPHA2-AS1/2-silenced MDA-MB-231 cells. Bioinformatics analyses identified 545 overlapping differentially expressed genes that were significantly up- or down-regulated by these treatments. Subsequent functional enrichment analyses of the overlapping genes in combination with in vitro assays indicated that EPHA2-AS1/2 may promote the proliferation and migration of MDA-MB-231 cells through the EPHA2 -dependent Ras signaling pathways mediated by MAPK8/JNK1, MAPK9/JNK2-NFATC2/NFAT1 (proliferation and migration) and JUND (migration). These results thus suggest that EPHA2-AS1/2 may represent a potential molecular target for triple-negative breast cancer treatment.